Recreational fishing effort and how management actions can affect it—Part 1: Theory - Edward Camp; Micheal S. Allen; Thomas T. Ankersen; Savanna Barry; Mark W. Clark (EDIS)
Recreational fishing is especially important to Florida’s economy and ecosystems. One of the most important metrics of recreational fisheries is “effort”—defined as the number of trips taken during a time and place. Effort is so important because it directly affects fish population sustainability, economic value and market activity. But what determines fishing effort? This publication describes the mechanisms that drive fishing effort. It specifically details the processes by which management actions can directly and indirectly affect fishing effort, and how feedbacks between these actions can change effort. The information in this document is critical for people involved with management decisions, like agency personnel and their stakeholders; those wanting to explain it to others, like extension agents; directly affected stakeholders like recreational fishers and guides; or simply the general public who want to know more about recreational fisheries in Florida.